Book review: The critical simulation of the textbook: irony and subversion for disciplinary transformation - Sofía Pérez Gil (Revista CIDOB d'Afers Internacionals)
Review of the book: Tickner, Arlene B. y Smith, Karen (eds.). International Relations from the Global South: worlds of difference. Routledge, 2020, 368 págs.